The Stars Shine Down - Sheldon, Sidney (London HarperCollins Publishers, 1993)
Lara Cameron, a young and beautiful self-made tycoon, has worked relentlessly for success, power and control of her life and personal relationships. But a discarded lover has vengeance in mind. By the author of "The Other Side of Midnight", "Master of the Game" and "Rage of Angels".
English Fiction.
Keywords: Business